Expressions spoken by vaccinated people: a moment of prevention (Research, Society and Development, 2022)
The objective of this research was to understand and report the perception of adult workers at the time of vaccination. It was selected 33 adults to answer the questionnaire, with a quantitative and qualitative approach, which analyzed the speeches and phrases during the extra wall vaccination process. The interview comprised men and women over 18 years old. The results showed that the herd effect impacting on the immunization of adults in extra -wall vaccination with speeches referring to the process of pain and anguish associated with collective suffering. The most prominent of the expressions reported were "fear" and "agony". It is interesting to note that all expressions intrinsically carry a mixture of pain, fear, imposition, and dread, associated with the vaccination process and affective/traumatic memories from the population's past. The nursing professional in this perspective has an essential role as an educator and supervisor of the provision of health services in the vaccination room. As a professional who works directly with the population a nurse has the responsibility to demystify doubts about the effectiveness and possible adverse events resulting from vaccination, in order to strengthen the NIP and consequently promote greater adherence to the program.